Ultrastructural characteristics of finger-like membrane protrusions in cell competition. (8th April 2022) - Kamasaki, Tomoko; Uehara, Ryota; Fujita, Yasuyuki
Abstract: A small number of oncogenic mutated cells sporadically arise within the epithelial monolayer. Newly emerging Ras- or Src-transformed epithelial cells are often apically eliminated during competitive interactions between normal and transformed cells. Our recent electron microscopy (EM) analyses revealed that characteristic finger-like membrane protrusions are formed at the interface between normal and RasV12-transformed cells via the cdc42–formin-binding protein 17 (FBP17) pathway, potentially playing a positive role in intercellular recognition during apical extrusion. However, the spatial distribution and ultrastructural characteristics of finger-like protrusions remain unknown. In this study, we performed both X – Y and X – Z EM analyses of finger-like protrusions during the apical extrusion of RasV12-transformed cells. Quantification of the distribution and widths of the protrusions showed comparable results between the X – Y and X – Z sections. Finger-like protrusions were observed throughout the cell boundary between normal and RasV12 cells, except for apicalmost tight junctions. In addition, a non-cell-autonomous reduction in protrusion widths was observed between RasV12 cells and surrounding normal cells under the mix culture condition. In the finger-like protrusions, intercellular adhesions via thin electron-dense plaques were observed, implying that immature and transient forms of desmosomes, adherens junctions or unknown weak adhesions were distributed. Interestingly, unlike RasV12-transformed cells, Src-transformed cells form fewer evident protrusions, and FBP17 in Src cells is dispensable for apical extrusion. Collectively, these results suggest that the dynamic reorganization of intercellular adhesions via finger-like protrusions may positively control cell competition between normal and RasV12-transformed cells. Furthermore, our data indicate a cell context–dependent diversity in the modes of apical extrusion.